Hubungan Perilaku Phubbing dengan Interaksi Sosial: (Literature Review) - Habibila Salwa Jenny; Isabelle Clara (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
The development of digital technology, particularly the use of smartphones, has transformed patterns of communication and social interaction within society. One phenomenon that has emerged is the behavior known as “phubbing,” which refers to the act of ignoring one’s conversation partner by focusing one’s attention on a smartphone during face-to-face interactions. This study aims to examine the concept of phubbing in the context of social interaction, identify the phenomenon as it occurs in society, and analyze its impact on the quality of interpersonal relationships. The method used is a literature review with a qualitative approach through the examination of various relevant scientific journal articles from the past seven years. Data collection was conducted via a documentary study, while data analysis employed a qualitative descriptive method by comparing and synthesizing findings from previous research. The results of the study indicate that phubbing behavior generally has a negative impact on social interaction, such as a decline in communication quality, reduced empathy, the emergence of conflicts, and low satisfaction in social relationships. Influencing factors include the intensity of smartphone use, low self-control, and the influence of digital culture. However, in certain contexts, such as the workplace, phubbing does not always have a negative impact. Therefore, awareness in the use of technology is necessary to ensure it does not disrupt the quality of social interactions.